DEVELOPMENT ECOTOURISM MARINE KUALA MERBAU BEACH VILLAGE KUALA MERBAU, DISTRICT OF PULAU MERBAU, KEPULAUAN MERANTI REGENCY OF RIAU PROVINCE - Siti Aisyah; Eni Yulinda; Hazmi Arief (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2018)
ABSTRACT The research was implemented in May 2018 in Kuala Merbau beach village merbau island Regency Kepulauan Meranti of Riau Province. This study aims to determine the general picture of ecotourism which is owned by Kuala Merbau beach made as a tourist destination. The research method used survey methods. The object of this study is the Kuala Merbau beach and respondents of this study were local residents, tourists and the government.The results of this study indicate that development owned Turkish Kuala Merbau large enough to be a tourist destination in Kepulauan Meranti. Based on the ecology of coastal waters and the geographical location of the beach that the development of marine ecotourism Kuala Merbau beach that was developed is the beauty of the landscape around the beach, activities such as swimming, rowing boat activity and the activity of the sailboat. So far the government's role in the development of ecotourism infrastructure Kuala Merbau beach there are some not yet available because it is still in the process of development by local communities but the beach is already included in the destination attractions in Kepulauan Meranti.Keywords: Development, Ecotourism Marine, Kuala Merbau